A novel framework for integrating social media as cooperative learning tool in higher education's classrooms - Mostafa Hamadi; Jamal El-Den; Sami Azam; Narumon Cherry Sriratanaviriyakul (The Asia-Pacific Society for Computers in Education (APSCE), 2021)
Abstract Despite the considerable body of literature on social media (SM)'s use as formal educational tools within universities, little has been done to provide a comprehensive adoption framework for SM as cooperative learning (CL) instruments. Nonetheless, the pedagogical arguments for SM's use in HE have theory support. This paper proposes an original SM integration framework based on CL methods within higher education (HE). An integrative review of relevant literature followed by a thematic review of six peer-reviewed empirical research and a thorough examination of relevant SM adoption models are conducted to identify commonalties and themes. In total, six themes were identified and incorporated as major components in the proposed framework. To the best of our knowledge, no previous research has proposed a framework that incorporates CL principles to support an effective SM integration process in HE. This paper proposes a novel integration framework which is a theoretically driven pedagogical guide for incorporating SM in HE's classrooms. It provides valuable insights on SM's use in education and forms the basis for future quantitative and qualitative (framework-testing) research in this area of study.